Platelets from COVID-19 Patients Show an Altered Nitric Oxide/Reactive Oxygen Species Production Balance - Petito, Eleonora; Guglielmini, Giuseppe; De Robertis, Edoardo; Becattini, Cecilia; Franco, Laura; Falcinelli, Emanuela; Conti, Chiara; Gori, Fabio; Vaudo, Gaetano; Cerotto, Vittorio; Paliani, Ugo; Mezzasoma, Letizia; Camilloni, Barbara; Gresele, Paolo; COVIR study investigators (Thrombosis and Haemostasis, 2025)
Oxidative stress has been associated with COVID-19-related thrombotic complications. No investigations have explored nitric oxide (NO) and radical oxygen species (ROS) production by platelets. Indeed, activated platelets generate both NO and ROS which in turn regulate platelet function. The aim of the present study was to measure platelet NO and ROS production in COVID-19 patients, to assess whether they correlate with disease outcome and to clarify the mechanisms of platelet NO/ROS imbalance in COVID-19.Hospitalized mild and severe COVID-19 patients, age- and sex-matched healthy controls, and patients hospitalized in intensive care units for reasons different from COVID-19 were enrolled. Platelet NO and ROS production was assessed by flow cytometry. The oxidant and antioxidant capacity of COVID-19 plasma was assessed using lipid peroxidation and ORAC assays. The effect of COVID-19 plasma on platelet NO production and the impact of antioxidants on it were studied by flow cytometry.Platelets from COVID-19 patients displayed an altered NO/ROS balance, with defective NO and increased ROS production. Platelet NO production was significantly lower in patients who developed thrombotic events during hospitalization. COVID-19 patients showed significantly increased plasma lipid peroxidation and reduced antioxidant capacity compared with healthy controls. Concordantly, plasma from COVID-19 patients impaired NO production by healthy control species platelets, which was restored by the antioxidant agent Hydroxy-TEMPO.Our findings suggest that the unbalanced platelet NO/ROS production in COVID-19 plays a role in the thrombotic complications of SARS-CoV-2 infection. The restoration of platelet NO production may represent a therapeutic target for the prevention of thrombotic events in COVID-19 patients.
Keywords: COVID-19; nitric oxide; platelets; reactive oxygen species; thrombosis